From Dharma Yuddha to Modern Warfare: An Analysis of War Ethics and Human Rights in Legal Perspective - Dr. Anjali Verma (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The ethical challenges of war are as ancient as war itself. Civilizations throughout history have grappled with the question: how can one engage in war justly? The Ramayana, a seminal epic in Indian culture, articulates the idea of Dharma Yuddha, or righteous war, governed by ethical codes. This framework emphasizes principles such as honor, non-violence against non-combatants, and moral restraint. In contrast, modern warfare is regulated through codified laws such as the Geneva Conventions, which seek to minimize human suffering and ensure accountability. This research paper analyses the metamorphosis in warfare ethics from Dharma Yuddha-which is derived from Indian Ancient philosophy and depicted in the Ramayana-to the modern international codification of conduct in war under International Humanitarian Law and International Human Rights Law. It tries to explore the historical, philosophical, and legal basis of how societies comprehend and regulate armed conflicts.